Ulysses Plasma Parameters:Latitudinal, Radial, and Temporal Variations - Goldstein, B. E.; Neugebauer, M.; Phillips, J. L.; Bame, S.; Gosling, J. T.; McComas, D.; Wang, Y. M.; Sheeley, N. R.; Seuss, S. T. (2004)
Observations by the Ulysses SWOOPS plasma experiment are used to investigate spatial and temporal gradients during the mission, with emphasis on more recent high latitude opbservations including the recent South Pole to North Pole passage during solar minimum.